2009
DOI: 10.1111/j.1365-294x.2008.04055.x
|View full text |Cite
|
Sign up to set email alerts
|

History and evolution of alpine plants endemic to the Qinghai‐Tibetan Plateau: Aconitum gymnandrum (Ranunculaceae)

Abstract: How Quaternary climatic oscillations affected range distributions and intraspecific divergence of alpine plants on the Qinghai-Tibetan Plateau (QTP) remains largely unknown. Here, we report a survey of chloroplast DNA (cpDNA) and nuclear ribosomal internal transcribed spacer (ITS) DNA variation aimed at exploring the phylogeographical history of the QTP alpine endemic Aconitum gymnandrum. We sequenced three cpDNA fragments (rpl20-rps12 intergenic spacer, the trnV intron and psbA-trnH spacer) and also the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
247
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(282 citation statements)
references
References 60 publications
(89 reference statements)
30
247
3
Order By: Relevance
“…This conclusion is supported by the unimodal mismatch distribution of the northeastern populations (Figure 4a), suggesting historical population expansion, and by the star-shaped phylogeny of haplotypes derived from haplotype A (Figure 2), the reduced levels of haplotypic and nucleotide diversity (Table 1), and the prevalence of haplotype A in the northeastern populations (Figure 1). The homogeneous genetic pattern in the northeastern populations is consistent with the AMOVA result, which showed relatively low genetic variation among populations (48.7%) in comparison with other alpine plant species on the Plateau (Chen et al, 2008;Yang et al, 2008;Wang et al, 2009). These patterns are consistent with the results of a simulation study in which sudden expansion from a few populations produced reduced allele diversity and areas of genetic homogeneity (Avise, 2000).…”
Section: A Shimono Et Alsupporting
confidence: 80%
See 2 more Smart Citations
“…This conclusion is supported by the unimodal mismatch distribution of the northeastern populations (Figure 4a), suggesting historical population expansion, and by the star-shaped phylogeny of haplotypes derived from haplotype A (Figure 2), the reduced levels of haplotypic and nucleotide diversity (Table 1), and the prevalence of haplotype A in the northeastern populations (Figure 1). The homogeneous genetic pattern in the northeastern populations is consistent with the AMOVA result, which showed relatively low genetic variation among populations (48.7%) in comparison with other alpine plant species on the Plateau (Chen et al, 2008;Yang et al, 2008;Wang et al, 2009). These patterns are consistent with the results of a simulation study in which sudden expansion from a few populations produced reduced allele diversity and areas of genetic homogeneity (Avise, 2000).…”
Section: A Shimono Et Alsupporting
confidence: 80%
“…Recent phylogeographic studies have examined the demographic history of alpine plants across the Plateau (Chen et al, 2008;Yang et al, 2008;Wang et al, 2009). Wang et al (2009) suggested that Aconitum gymnandrum has survived on high-altitude parts of the central Plateau throughout the Quaternary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population structure of Aconitum gymnandrum (Ranunculaceae) recovered two genetic diversification centers on the platform, suggesting that this cold-tolerant species may have survived in some ice-free places on the TP platform during the Quaternary glaciations (Wang et al, 2009). The scenario may be applicable to interpret the origin of Przewalskia.…”
Section: Biogeographic Diversification On the Tibetan Plateaumentioning
confidence: 99%
“…In contrast, studies on the Asian biota have been rather limited. The complex topography of East Asia probably provided refugia for species during times of Pleistocene glaciation [14], yet only a few plant and bird species restricted to the Qinghai-Tibetan Plateau (QTP) have been evaluated [15][16][17][18][19][20].…”
mentioning
confidence: 99%